(untitled) (Homoeopathy for All, 2023)
Eye infections are a common medical presentation and can range in severity from being relatively mild and self-limiting to potentially causing serious vision-threatening complications. While many eye infections tend to resolve on their own, some have the potential to lead to corneal scarring or even permanent blindness. Prompt diagnosis and appropriate treatment are essential for preventing complications and preserving good vision.